Lipase-catalyzed synthesis of poly(ω-pentadecalactone-co-globalide) in supercritical carbon dioxide - Santos R.D. (2024)
© 2024 Elsevier B.V.This work investigates the enzymatic ring-opening polymerization of poly(ω-pentadecalactone-co-globalide) using supercritical carbon dioxide as a solvent. Copolymerizations were carried out in a high-pressure variable-volume view cell to evaluate the influence of CO2:monomers mass ratios and the use of chloroform as a cosolvent. Also, Novozym® 435 and Lipura® Flex were compared as catalysts. The highest molar mass obtained with the use of a cosolvent (Mn = 24,380 g mol−1) was achieved in the 1:2:1 (CO2:monomers:chloroform) condition, reflecting the combined effect of the cosolvent and a higher concentration of the monomers, while reactions without it showed better results for molar mass (Mn up to 27,902 g mol−1). Dispersity was higher when a cosolvent was used (Dispersity up to 7.51) than reactions with supercritical carbon dioxide only (Dispersity up to 5.36). Monomer conversions above 97 % and reaction yields from 55.77 wt% up to 79.61 wt% were achieved for copolymerizations with and without a cosolvent, using Novozym® 435 as catalyst. Lipura® Flex produced copolymers with high molar mass (Mn up to 21,605 g mol−1), reaction yields up to 73 wt%, and monomer conversions from 82 % to 96 %.